Książki wyzwalają emocje - Żórawska, Natalia (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
This article is a review of the book by Ryszard Koziołek entitled „Dobrze się myśli literature” (Literature is a good way of thinking). This publication is a collection of essays in which the literary expert considers the essence of contemporary reading. Koziołek pays special attention to emotions accompanying reading – bot the latest literature and the books considered to be classic ones. He indicates that literature is a special kind of continuity which can be analyzed through the prism of many fields of science, among others, economics or psychology.
Books release emotions
Rec.: Ryszard Koziołek, „Dobrze się myśli literaturą”, Wydawnictwo Czarne, Wołowiec 2016, 288 ss.
Keywords: Ryszard Koziołek; essay; literary study; history of Polish literature; esej; literaturoznawstwo; historia literatury polskiej